Diversidade genética e efeitos da secagem e salinidade na propagação do jenipapeiro - Cardoso, Milena Nascimento (2019)
The genip tree (Genipa americana L.) is a native tree from Brazil, belonging to the Rubiaceae family. This tree is widely prominent both in its spatial distribution – occurring from Mexico to Patagonia – and in its forms of use. This is a late successional species indicated for forest restoration areas, and its fruit –genipap – presents pharmacological activities and consequent commercial potential. The destruction of natural habitats for this species, coupled with their extensive use justify a greater demand for research. Studies on genetic diversity in natural populations, and on the mastery of technical knowledge about their propagation are crucial for providing essential criteria for pre-breeding, conservation strategies and commercial exploitation of genipap. The objective of this study was to characterize germination (drying and salinity) and genetic aspects in populations of Genipa americana L. Genetic diversity was estimated by ISSR markers in 15 natural populations of genip tree from the state of Sergipe, Brazil. In the study of the influence of drying, the seeds were benefited and submitted to different drying periods (0; 24; 48; 72; 96 and 120 h) at 28 ºC ± 2 ºC and sown in polyethylene bags containing commercial substrate and powdered manure. To evaluate the effects of saline stress on seed physiological potential and growth in vitro, the seeds were submitted to different NaCl concentrations (0; 25; 50; 75 and 100 mM). Every 72 h embryonic axes were extracted to determine the activity of antioxidant enzymes superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APX). To verify the initial growth under salinity in vitro, accessions explants NB, SA and SF were inoculated in MS medium plus concentrations 0; 25; 50; 75 and 100 mM and evaluated after 90 days. Proline was quantified at 30, 60 and 90 days after inoculation of the explants in saline medium. In the propagation experiments, a completely randomized design with four replications of 25 seeds was used, totaling 100 seeds per treatment. High polymorphism rate (100%), 0.36 Shannon index and division of individuals into two distinct groups were found. Viability was maintained at 80% in the 48h drying period, when humidity was 32% and the initial growth was affected after 96 h of drying. The 50 mM NaCl concentration was found to affect seed physiological potential and salinity increased the activity of SOD and APX enzymes up to 288 hours of exposure to saline stress. Saline stress causes a decrease in in vitro growth of the species, and the SA access showed higher tolerance to salinity. Salt increase in the medium caused proline increase at 30, 60 and 90 days, indicating its use as a biochemical marker for stress in genip trees.